The Balancing Educational Finance through Power Equalizing Models - Dinda Febrianti Putri; Sevia Diana Safitri; Ahmad Abdullah Zawawi (Education and Sociedad Journal, 2024)
This research examines the implementation of the Power Equalizing Model in educational financial management to improve the efficiency and transparency of fund allocation. By integrating key elements such as stakeholder participation, technology utilization, and innovative economic strategies, this model aims to create a more equitable and accountable system. The study employed a qualitative approach through interviews with educators, educational managers, and technology developers to identify the benefits and challenges of applying the model. Findings indicate that the Power Equalizing Model enhances transparency and accountability in managing education funds. However, issues such as stakeholder coordination and adaptation to technological tools remain obstacles to optimal implementation. The research concludes that integrating participatory and technological innovations is essential to achieving more effective and fair educational financial governance. These insights are expected to contribute to developing more inclusive and sustainable education financial management practices in the future.